Impact of ozone on the water relations of ash (Fraxinus excelsior L.) - Reiner, Susann. (1996)
During the field seasons 1993 and 1994, five-year-old field-grown ash trees as well as potted two-year-old saplings and one-year-old seedlings of ash (Fraxinu. g exccl. 5ior L. ) were exposed to ozone episodes in open-top chambers. The plants received either charcoal-filtered air (CF) or charcoal-filtered air to which 150 ppb of ozone were added (CF+03). Plants in unchambered plots, receiving ambient air (Ambient), were included into the investigation for comparison. Half of the two-year-old saplings of each of the three pollution treatments were subjected to three drought cycles of 7-14 days, while the rest of the plants were well watered as a control. The two-year-old saplings were the main object of the investigation. On these, the main parameters investigated were: stomatal conductance; the growth parameters - extension growth, radial increment at the stembase and radial increment at the base of the new shoot; leaf area; aboveground biomass production; the microscopic determination of ringwidth; and the structure of the latest annual ring for samples taken from the stembase. Additionally, stomatal conductance was measured in the five-year-old trees and total biomass accumulation, photosynthate allocation and ring parameters of the latest annual ring were investigated in the one-year-old seedlings. The ozone episodes were shown to influence stomatal conductance in plants of different water status differently. Drought stress led to a significant decrease of stomatal conductances, and the drought-ozone interaction caused a further decrease which was also significant. The ozone episodes also affected stomatal responsiveness of the plants, restricting stomatal aperture of the droughted two-year-old saplings, when the drought cycles were finished and the plants were maintained at high soil moisture again. The drought cycles alone, however, left the functioning of the stomata unimpaired. The restriction of stomatal aperture which was found for the droughted CF+03 treatment caused reductions of growth and biomass accumulation, but a significant decrease was found only for radial growth at the stembase of those plants. Analysis of the annual rings showed that this was caused by a reduction of xylem growth, while phloem development did not seem to be affected. Radial increment at the base of the new shoot was less affected by the pollution treatment. Here only a significant impact of the drought could be found, and the growth reduction was less pronounced. In the well-watered plants, ozone caused a slight increase in stomatal conductance which led to increased aboveground biomass accumulation, but concomitantly biomass allocation was slightly altered, favouring the crown rather than the lower plant organs. A reduction of photosynthate allocation to the roots became evident from measurements on the one-year-old saplings. Due to chamber effects, stomatal conductance as well as growth, biomass accumulation and allocation differed from those of plants from the Ambient treatment. The responses to ozone that were found in this study could lead to increased crown growth during periods of good water availability and to a strong reduction of water uptake during and following drought conditions. Thus crown demand for water may increase in ash trees exposed to elevated ozone concentrations, while the supply of water to the crown may become limiting.